The use of Concordance for Teaching Vocabulary: A Data-driven Learning Approach. (2nd June 2015) - Yılmaz, Enes; Soruç, Adem
Abstract: Lexical knowledge and opportunities or tools for learning new vocabulary words have increasingly become important over the last four decades. But, using concordance as a new tool for this purpose has not gained much attention. The present research, therefore, aims to find out, if any, whether concordance as a reference tool has an impact on teaching or learning vocabulary in an EFL setting. As an experimental study, this research involved two groups of students conveniently. One was experimental group; the other control. While the former was exposed to electronic concordance program (COCA), the latter was controlled by using traditional vocabulary instruction. Pre/post-test results showed that the class receiving vocabulary through concordance performed much more than the control class which received traditional vocabulary instruction. And further analysis revealed that the performance was statistically significant. In addition, the interviews randomly held with the students also supported the quantitative results. Some implications are given and a variety of suggestions made for language teachers at the end.